Physico-Chemical, Microbiological and Sensory Quality of Chicken and Beef Stored in Home Refrigerator - Md Adnan, Md Adnan; Yadav, Sunil; Kumar Yadav, Saroj; Alam, Mahabub (Journal of Meat Science, 2026)
The purpose of this study was to ascertain how long raw chicken meat and  beef meat kept at 4°C in a typical home refrigerator would last. Researchers  from Chattogram Veterinary and Animal Sciences University performed an  extensive examination over five days, assessing 10 meat samples (five chicken  meat and five beef meat) obtained from local markets in Chattogram (Jhawtola,  Bahaddar Hat, and Chawk Bazar). The quality assessment encompassed  physico-chemical, microbiological, and sensory criteria, including pH, water holding capacity (WHC), extract release volume (ERV), protein degradation  (tyrosine value), fat oxidation (TBARS), total viable microbial count (TVC),  and aroma. Significant data indicated a gradual deterioration in quality for  both types of meat. Sensory evaluation indicated a significant escalation in offodours, becoming especially evident by the fifth day. Physicochemical research  revealed a steady decrease in pH for chicken, whereas beef pH exhibited  greater variability. The water-holding capacity was minimal for both meats on  the penultimate day. Moreover, elevated tyrosine and TBARS levels indicated  continuous breakdown of proteins and lipids, respectively. Microbiologically,  beef had a greater overall viable count compared to chicken. The study revealed  that whereas beef demonstrated a more rapid decomposition rate, both meats  underwent considerable quality degradation by the fifth day of refrigerated  storage. These findings point out the importance of appropriate raw meat  handling and timely storage techniques for preserving domestic food safety  and quality.
Keywords: Physicochemical properties; microbiological analysis; sensory evaluation; chicken meat; beef meat; home refrigeration